Stepping up our approach to the management of infants with fever without a source. Issue 9 (September 2017) - Halpert, Karen; Mounsey, Anne; O'Mara, Heather
Abstract : PRACTICE CHANGER : The Step‐by‐Step approach is the most sensitive algorithm for the management of infants with fevers without a source in the emergency department (ED), allowing providers to decrease invasive testing and antibiotic treatment of low‐risk infants. Strength of recommendation: B, based on a multicenter prospective study Gomez B, Mintegi S, Bressan S, Da Dalt L, Gervaix A, Lacroix L; European Group for Validation of the Step‐by‐Step Approach. Validation of the "Step‐by‐Step" approach in the management of young febrile infants. Pediatrics . 2016; 138(2). doi: 10.1542/peds.2015–4381.